2000
DOI: 10.1128/jvi.74.16.7431-7441.2000
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Retrovirus Capsid-Nucleocapsid Proteins in the Presence of Membranes or RNA

Abstract: Retrovirus Gag precursor (PrGag) proteins direct the assembly of roughly spherical immature virus particles, while after proteolytic processing events, the Gag capsid (CA) and nucleocapsid (NC) domains condense on viral RNAs to form mature retrovirus core structures. To investigate the process of retroviral morphogenesis, we examined the properties of histidine-tagged (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…For NMR studies, the proteins were dialyzed against 50 mM sodium phosphate (pH 5.5), 100 mM NaCl, and 5 mM dithiothreitol (DTT) and then concentrated by Millipore ultrafiltration concentrators against the same buffer. Protein purities were evaluated after fractionation by SDS-PAGE (32,33,(57)(58)(59)(60)(61) by Coomassie Blue staining (32,(57)(58)(59). The HIV NC peptide was prepared commercially as reported previously (61).…”
Section: Methodsmentioning
confidence: 99%
“…For NMR studies, the proteins were dialyzed against 50 mM sodium phosphate (pH 5.5), 100 mM NaCl, and 5 mM dithiothreitol (DTT) and then concentrated by Millipore ultrafiltration concentrators against the same buffer. Protein purities were evaluated after fractionation by SDS-PAGE (32,33,(57)(58)(59)(60)(61) by Coomassie Blue staining (32,(57)(58)(59). The HIV NC peptide was prepared commercially as reported previously (61).…”
Section: Methodsmentioning
confidence: 99%
“…Final liposome lipid concentrations were 0.4 mg/ml cholesterol and 1.6 mg/ml of either PC or PS, and liposomes were stored for up to 1 month under nitrogen at Ϫ20°C. Monolayer membrane binding assays were modified from the monolayer binding assays described by Zuber et al (63). One-hundred-microliter samples containing 200 to 300 nM protein in monolayer buffer (25 mM sodium phosphate [pH 7.8], 50 to 125 mM NaCl) were deposited into 15-mm-wide, 1.5-mm-deep glass depression (Boerner) slides.…”
Section: Methodsmentioning
confidence: 99%
“…While HIV-1 MA associates in solution and in 3D crystals as trimers, the capsid domains of retroviruses tend to organize into hexamer rings (3,4,6,7,25,27,30,31,32,34,37,39,40,63). These observations have prompted several researchers to incorporate MA trimers into PrGag hexamer models by postulating that trimers form nodes which interconnect hexamers and that two MA members from each of three trimer units position themselves in a p3 fashion over CA hexamers (15,48).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that nucleic acid greatly increases the efficiency of particles assembly, that the size of these particles was dependent on the size of the RNA, and that treatment of particles with ribonuclease triggered disassembly. 81,82 Later studies performed on MLV and HIV-1 particles generated in mammalian cells have demonstrated that, in the absence of viral gRNA, VLPs specifically package cellular mRNAs randomly, as mRNA species detected in VLPs are in proportion to their cellular levels, 24,83,84 at the exception of some RNA species such as 7SL, and U6 RNAs, that are specifically enriched in wild-type HIV-1 and MLV particles and whose function remains unclear. 24,25,83,84 Interestingly, retroviral cores containing either viral or cellular RNAs were disassembled by RNase treatment, 83 confirming the importance of the RNA-Gag interaction in the formation and structure of retroviral particles.…”
Section: Gag-rna Complexes Nucleate Retroviral Assemblymentioning
confidence: 99%